(untitled) (Biological Sciences - PJSIR, 1994)
Several new complexes of zirconium (IV) containing a number of monodentate and multidentate organic ligands have been synthesized and characterized. The complexes have the compositions. [Zr(O)C12(en). Hpl. [Zr(O)C1z.2L.Hpl. [Zr.L’3Cl1 and [Zr(O)C12.L"1 [en = ethylenediamine; L = triphenylphosphine oxide. triphenylarsine oxide. pyridine or aniline; L’=8-hydroxoquinolino. o-aminophenoxide, L" = diethylcnetriamino and triethylenetctramino]. The molar conductance data indicate that complexes [Zr(C9H6NO)3Cll and [Zr(C6H4NHP)3Cll are 1:1electrolytes but all other complexes behave as 2:1electrolytes. The experimental data are consistent with six-fold coordination of Zr (IV) ion in all the complexes excepting [Zr (C9H6NO)3Cl] [Zr(C6H4NHP)3Cl] and [Zr(O)C .tet] which are seven coordinated.